Rare occupational respiratory diseases - Anna Witkowska; Marta Wiszniewska; Jolanta Walusiak-Skorupa (Nofer Institute of Occupational Medicine, 2020)
This paper reviews rare occupational respiratory diseases with uncommon causes. Among others, it refers to the Ardystil syndrome characterized by the occurrence of organizing pneumonia in the textile printing sprayers, as a result of inhalation of substances used in aerographic textile printing. Furthermore, secondary pulmonary alveolar proteinosis due to exposure to chemical and organic dusts was described, and so was the occurrence of the "vineyard sprayer's lung" in farm workers in Portugal. Eosinophilic bronchitis, showing a strong resemblance to bronchial asthma, was found to occur, among others, in a baker, a nurse and workers exposed to acrylates, α-amylase or welding gases. Occupational exposure to diacetyl in popcorn production workers might also create a threat to their respiratory system. A newly recognized factor that may cause bronchitis and lung diseases is the fiberglass used by workers building small boats and ships. An increased risk for respiratory ailments is observed in people employed in the textile industry, exposed to commodities or cotton dust. Even the resources used to protect different surfaces against moisture have been recognized as the causative agents of lung diseases. The rare occurrence of some occupational respiratory diseases enables a detailed analysis of the epidemiology and evaluation of the relationship between the etiologic agents and the development of the disease. This literature review highlights the fact that most respiratory diseases require a special analysis of occupational and environmental exposure. Med Pr. 2020;71(1):89-104